Antimemetics: why some ideas resist spreading - Asparouhova, Nadia (Dark Forest Collective, 2025)
"It's easier than ever to share ideas, yet some of the most interesting ideas are burrowing deeper underground, circulating quietly among group chats, texts and whisper networks. While memes -- self replicating bits of culture -- thrive in an attention-driven economy, other ideas are becoming strangely harder to find. Antimemetics: Why Some Ideas Resist Spreading explores this paradox, uncovering the hidden forces that determine what we remember, what we forget, and why some ideas -- no matter how compelling -- resist going viral."--Publisher description